Institutionalization of older French adults with dementia: Role of the informal carer's degree of kinship. Issue 8 (6th May 2021) - Huvent‐Grelle, Dominique; Ficheur, Grégoire; Beuscart, Jean Baptiste; Genin, Michaël; Vaudreuil, Claire; Boulanger, Eric; Puisieux, François
Abstract: Background: The institutionalization of a patient with Alzheimer's disease or other dementia (ADOD) is the last resort for the latter's family and/or caregivers. We hypothesized that the degree of kinship between the patient and his/her caregiver would influence the likelihood of institutionalization. Objective: To assess the association between institutionalization of patients with ADOD and the degree of kinship with the family caregiver. Methods: A cross‐sectional study of patients with ADOD aged 75 or over attending a memory center in France for the first time between 2011 and 2014, as recorded in the French National Alzheimer Database. Multivariable logistic regression was used to assess factors associated with institutionalization after adjustment for age, sex, the Mini‐Mental State Examination score, educational level, and type of dementia. Results: A total of 52, 874 patients were included. The primary caregiver was most often a child (54.8%) or the spouse (36.7%). Compared with the "spouse" reference category, all the other caregiver categories were associated with a significantly greater likelihood of institutionalization; the odds ratio [95% confidence interval] was 4.68 [3.67–5.92] when the carer was a grandchild, 5.48 [4.93–6.09] for a child, 4.93 [4.11–5.91] for a daughter‐/son‐in‐law, 8.76 [7.15–10.70] for a sibling, and 8.93 [7.48–10.65] for a niece/nephew. Conclusion: The likelihood of institutionalization of older patients with ADOD varied with the degree of kinship. Compared with the "spouse" reference category, the likelihood was higher for all other types of caregivers but was especially high when the caregiver was not a direct descendant of the patient.